Study of serum bilirubin as a diagnostic method to predict acute perforated appendicitis - Marimuthu, Valarmathi; Ilamparuthi, Chiddharth Venkateshan (International Surgery Journal, 2021)
Background: Acute appendicitis is the commonest cause of ‘acute surgical abdomen’. Appendicectomy is the most frequently performed urgent abdominal operation and is often the first major procedure performed by a surgeon in training. The aim of the study was to whether hyperbilirubinemia might be used as a diagnostic tool to predict perforated appendicitis. Methods: This study comprised patients who presented with the condition of appendicitis and abnormal liver function tests on admission and had a laparoscopic or open appendectomy. The age information, duration of symptoms, temperature, white blood cell counts, bilirubin levels, and histology data were gathered. Peritoneal fluid was cultured and examined for sensitivity. Results: The average bilirubin level of all participating patients was 0.92 mg/dl (range, 0.1-4.3 mg/dl). The mean bilirubin levels were higher for patients with simple appendicitis compared to those with a non-inflamed appendix (0.7 mg/dl and 0.4 mg/dl, p<0.001). Hyperbilirubinaemia was reported to have a specificity of 89% and a positive predictive value of 90.02% for acute appendicitis. Patients with appendiceal perforation, however, had a mean bilirubin level of 1.7 mg/dl and were more likely to have hyperbilirubinaemia (p<0.001). The specificity of hyperbilirubinaemia for perforation or gangrene was 73%. Conclusions: Patients with hyperbilirubinemia with appendicitis condition should be screened for a greater risk of appendiceal perforation than those with normal bilirubin levels.